Dam-Break Simulation of the Sepaku Semoi Dam Using Zhong Xing Hy21 for Flood Hazard Mapping and Disaster Mitigation Planning - Avelina N. B. S. Pusoko; Wahyu Sejati; Eriv V. Aryadi (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2026)
Water is a vital resource for human survival, and its limited availability requires effective management, including dam construction. The Sepaku Semoi Dam in Indonesia has a storage capacity of 10 million m³ and a reservoir area of 280 hectares, serving to mitigate floods and supply raw water of 2,000 L/s to the National Capital (IKN) and 500 L/s to Balikpapan. Despite these benefits, dams pose risks of failure, particularly dam break events that may cause flash floods. This study analyzes the potential dam break of the Sepaku Semoi Dam due to piping phenomena using Zhong Xing HY21 software. The simulation assessed inundation extent, water depth, flood arrival time, inundation, and flow velocity. The PMF discharge was 1,537.50 m³/s, while the peak outflow discharge from the dam-break simulation reached 4,043.37 m³/s. The reported simulation time of 2.25 hours should be clarified as either flood arrival time, failure time, or time to peak outflow. Results indicate that overtopping does not lead to dam break, whereas bottom piping under design flood conditions produces the most severe impacts. Extreme piping scenarios result in flood inundation across five villages: Kel. Mentawir, Wono Sari, Suka Raja, Argo Mulyo, and Tengin Baru. According to the Decision of the Director General of Water Resources No. 257/KPTSD/D/2011 (Direktur Jenderal Sumber Daya Air, 2011), all five villages fall within Zone 1, with flood depths exceeding 0.6 m. Based on FEMA classification, Kel. Mentawir, Wono Sari, and Tengin Baru are categorized as extreme hazard, Argo Mulyo as high hazard, and Suka Raja as moderate hazard.